Determining the influence of ultra-dispersed aluminum nitride impurities on the structure and physical-mechanical properties of tool ceramics - Gevorkyan, Edwin; Nerubatskyi, Volodymyr; Chyshkala, Volodymyr; Gutsalenko, Yuriy; Morozova, Oksana (Eastern-European Journal of Enterprise Technologies, 2021)
This paper considers features related to manufacturing the chromium oxide-based tool material. The process involved ultra-dispersed powders made of aluminum nitride. It has been established that the destruction of chromium oxide at high sintering temperatures is prevented through the reaction sintering of chromium oxide (Cr2O3) and aluminum nitride (AlN). It was established that the structure of the composite depends both on the temperature and the duration of hot pressing. Thermodynamic calculations of the interaction between Cr2O3 and AlN showed that this interaction begins at a temperature of 1,300 °C. In contrast to hot pressing in the air, no СrN and Сr2N compounds were formed in a vacuum. With increasing temperature, the content of Al2O3 in solid solution becomes maximum at a temperature of 1,700 °C in the case of hot pressing in the air while in vacuum the content of Al2O3 remains unchanged within the entire temperature range of 1,300–1,700 °C. When increasing the time of hot pressing to 30 minutes, the size of individual grains reaches 10 μm. It has been shown that in the sintering process involving Cr2O3 and AlN, the plasma-chemical synthesis produces the solid solution (Cr, Al)2O3 at the interphase boundary, which improves the mechanical properties of the material. The influence exerted on the quality of the machined surface of tempered hard steel when machining by the devised tool material based on chromium oxide with an optimal admixture of 15 wt % of ultra-dispersed aluminum nitride powder was investigated. It was determined that the quality of the machined hard steel surface improved compared to standard imported tool plates. It was established that the resulting tool material, in addition to relatively high strength and crack resistance, also demonstrates high thermal conductivity, which favorably affects the quality of the machined steel surface, given that lubricants and coolants are not used during the cutting process.